2012
DOI: 10.2298/tsci120430174m
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of parameters affecting the heat generation in friction stir welding process

Abstract: Heat generation is a complex process of transformation of a specific type of energy into heat. During friction stir welding, one part of mechanical energy delivered to the welding tool is consumed in the welding process, another is used for deformational processes etc., and the rest of the energy is transformed into heat. The analytical procedure for the estimation of heat generated during friction stir welding is very complex because it includes a significant number of variables and parameters, and many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Figure 17. a) Temperature distribution in workpieces in plane normal to the joint line, b) temperature history (experimental and numerical) of specific discrete nodes, c) location of selected discrete nodes [56,57] Figure 16, a gives a rendered image of numerically estimated temperature in workpieces. Rendering is done for the moment the temperature reached maximal value -a few seconds before the tool shoulder was involved in the welding process.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 17. a) Temperature distribution in workpieces in plane normal to the joint line, b) temperature history (experimental and numerical) of specific discrete nodes, c) location of selected discrete nodes [56,57] Figure 16, a gives a rendered image of numerically estimated temperature in workpieces. Rendering is done for the moment the temperature reached maximal value -a few seconds before the tool shoulder was involved in the welding process.…”
Section: Resultsmentioning
confidence: 99%
“…The first phase of the research consisted of a number of experiments performed to isolate and prove the optimal dimensions and shape of a welding tool, usable welding process parameters, as well as investigation of parameters affecting the heat generation process. Welding was performed on the universal lathe and due to the complexity of the research, it was necessary to have two different measuring configurations [25,41]. The first configuration was used for capturing loads on the welding tool and base material (forces and torque) while the second configuration was used to estimate friction coefficient and contact pressure between the welding tool and base material.…”
Section: Experimental Researchmentioning
confidence: 99%
“…For example, Boeing applies FSW for the production of fuel tanks for Delta rockets, while Marine Aluminium from Norway uses this technique for joining large parts for ferry boats. Numerous studies of producing and testing of FSW joints can be found in the literature [2][3][4][5][6][7][8][9][10][11][12][13]. Regarding the joint geometry, butt joints are most often used in practice and analysed in the literature, e. g. [6,7,11].…”
Section: Introductionmentioning
confidence: 99%